Hybrid vigour over environments for yield and its components in bread wheat - Pancholi, S R; Sharma, S N; Sharma, Yogendra; Maloo, S R (Journal of Cereal Research, 2011)
Magnitudes of heterosis over mid-parent, better-parent and inbreeding depression were calculated in a 10 x 10 half diallel set of bread wheat (Triticum aestivum L. em. Thell.) for fourteen quantitative traits under three sowing conditions. Heterosis and heterobeltiosis for grain yield was mainly dependent upon biological yield per plant, grain weight per ear, 1000-grain weight and number of grains per ear. Sufficient degree of heterosis and heterobeltiosis was observed for all the characters. The crosses UP 2611 x PBW 533 in early sown, WH 786 x PBW 509, HD 2859 x PBW 509 and UP 2590 x HD 2859 in normal sown and WH 786 x JKW 8 and WH 786 x PBW 509 in late sown conditions, emerged as heterotic as well as heterobeltiotic crosses for yield per plant. The crosses HUW 567 x UP 2590 and Raj 4058 x